Knowledge, attitudes and practices of livestock and aquaculture producers regarding antimicrobial use and resistance in Vietnam - Pham-Duc, Phuc; Cook, Meghan A.; Cong-Hong, Hanh; Nguyen-Thuy, Hang; Padungtod, Pawin; Nguyen-Thi, Hien; Dang-Xuan, Sinh (Public Library of Science, 2019)
The use of antibiotics in livestock production is considered a major driver of antibiotic resistance on a global scale. In Vietnam, small- and medium-scale livestock producers dominate the domestic market and regulatory pushes have done little to decrease antibiotic use. In order to inform future policy directions, this study aims to explore knowledge, attitudes, and practices amongst livestock producers to identify their perspectives on antibiotic use and resistance. A total of 392 small- and medium-scale producers specialized in pig, poultry and aquaculture production participated in the study. The results showed that the primary reason for antibiotic use reported by producers was for the treatment of infections (69%). However, prophylactic use was also evident, with farmers reporting other reasons for antibiotic use such as “animals display abnormal symptoms or behaviour” (55%), the “weather is about to change” (25%), or “animals on neighboring farms fall ill” (27%). Only one-fifth of producers demonstrated favorable attitudes towards antibiotic use and preventing antibiotic resistance. Moreover, administering antibiotics remained the preferred countermeasure directly applied by farmers at the first indication of disease (17%), compared to enacting hygiene (10%) or quarantine (5%) measures. The results showed divergent trends amongst producers, with pig producers demonstrating higher levels of knowledge, more favorable attitudes, and higher self-reported utilization of good practice. Better knowledge, attitudes, and practices were also associated with producers who engaged in efforts to explore information on antibiotic use and resistance, which improved incrementally with the number of sources consulted and hours invested. However, there were some areas where increased knowledge or more favorable attitude scores did not translate into better practices. For instance, producers with higher levels of formal education performed significantly better than those with lower education in terms of knowledge and attitude, though both groups reported similar practices. The findings of this study may support future interventions to prevent both antibiotic misuse and the development of antimicrobial resistance.